2020
DOI: 10.3390/coatings10080733
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Thermal Annealing and Ferroelectric Capacitor Area Effects for Hafnium-Zirconium Oxide Devices

Abstract: In this study, we reveal that the thermal budget of post-metal annealing not only determines the formation of the ferroelectric phase and dipole domain but also the film quality of the gate stack in a metal-ferroelectric-metal capacitor. The higher leakage current caused by defect traps or grain boundaries within a gate stack would influence the stability of the ferroelectric domain switching. Furthermore, the ferroelectric domain switching and polarization current also depend on the ferroelectric capacitor ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The capacitor with scavenging showed outstanding performances compared to the capacitor without scavenging as well as other previous MFIS structures. 32,49–53…”
Section: Resultsmentioning
confidence: 99%
“…The capacitor with scavenging showed outstanding performances compared to the capacitor without scavenging as well as other previous MFIS structures. 32,49–53…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these materials are technologically important for many applications (e.g., ferroelectric memory, sensor and energy storage devices), and they have thus received continuous attention [2]. For example, Hsu et al found that the ferroelectric capacitor can dominate the transfer characteristics of a p-type SnO thin-film transistor through the modulation of series capacitance in the gate stack based on a one-transistor one-capacitor series configuration [3].…”
mentioning
confidence: 99%